Women and livestock challenge dialogue - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Global Challenge Dialogue on Women and Livestock is an e-consultation that involves knowledgeable and influential thinkers and doers from around the world in deepening understanding of the challenge, seeking ideas, and devising a strategy and action plan that will realize tangible impacts of fighting poverty through women and livestock. It includes creating new ways to empower women livestock keepers to further develop themselves, their families, their communities and their nations.